Pengaruh Motivasi Belajar Terhadap Akhlak Santriwati - Amrina, Awelna (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
Lack of motivation in a student will form an attitude that does not reflect the religious spirit of a student. Therefore, it is necessary to encourage the environment to increase the willingness of students to apply akhlakul karimah with the help of learning motivation. In this study, researchers used a quantitative descriptive approach. The population in this study were 127 people and in this study a purposive sampling sample was selected with a total sample of 22 respondents in the darnis karim dormitory. The results of the study are: first, there is a significant influence between learning motivation on the morals of santriwati as evidenced by statistical tests with a value of 0.000 0.05, so it is declared influential. Second, the influence between the independent variable (learning motivation) on the dependent variable (morals) is included in the very high category of 0.819 and the magnitude of the influence of these variables is 81.9%.